Ekonomi sirkular sebagai solusi pengelolaan sumber daya: Analisis konseptual dan aplikatif - TAUFIK, A. MUQIT (Maliki Interdisciplinary Journal, 2026)
A circular economy is a development approach that offers solutions to the problems of limited natural resources and increasing waste resulting from the implementation of a linear economic model. This article aims to analyze the concept of a circular economy and examine its application as a solution for sustainable resource management. The writing method uses a conceptual and applied approach through a literature review of various scientific sources, policies, and practices of the circular economy. The results of the study indicate that a circular economy emphasizes the principles of waste reduction, reuse, recycling, and product life cycle extension through design and technological innovation. The implementation of a circular economy contributes to increased resource efficiency, reduced environmental impacts, and the creation of economic added value and green jobs. However, the implementation of a circular economy still faces challenges such as limited regulations and infrastructure, as well as low public awareness and literacy. Therefore, integrated policies, technological support, and collaboration between the government, the private sector, and the community are needed to strengthen the transition to a sustainable and inclusive circular economy.